Habitual khat chewing induced oral erythroplakia: A case report - Aisha A.H. Al-Jamaei; Khaled Al-Kebsi; ElhamA. Al-Qafaf; Mayada H.M. Hanash; R.V. Subramanyam; Jan G.A.M. de Visscher (Oral Oncology Reports)
Oral erythroplakia (OE) is a clinical diagnosis of a relatively rare, solitary erythematous lesion. It has a high and significant risk of malignant transformation. OE is most commonly caused by tobacco use, especially smokeless tobacco, alcohol drinking, and chewing betel nut. We presented a case of a 53-years-old male who developed a large erythroplakia on his left buccal mucosa, likely induced by chewing khat. This patient had never used the tobacco or alcohol in any form. Given that chewing khat is quite common in some Middle East and African countries, it is essential for oral health care professionals to be aware of its potential development of erythroplakia and oral cancer.